AFFECTIVITY IN THE CLASSROOM: THE TEACHER-STUDENT RELATIONSHIP IN EARLY CHILDHOOD EDUCATION - Folha de Araújo Oliveira, Mirian (Revista Gênero e Interdisciplinaridade, 2025)
The child is a complex being, who needs his needs to be met as a whole, including his cognitive and affective needs. Teaching goes beyond the content, teaching involves having empathy, love and this happens through affection in interactions with others. This work aims to understand how affection can contribute to children’s learning in early childhood. It was carried out through bibliographical research, searching for authors who discuss the topic. Based on affection, the teaching and learning process becomes more meaningful and enjoyable, with the role of the teacher and the help of the family being essential.